2016
DOI: 10.1093/cvr/cvw015
|View full text |Cite
|
Sign up to set email alerts
|

THSD1preserves vascular integrity and protects against intraplaque haemorrhaging in ApoE−/−mice

Abstract: THSD1 is a new regulator of endothelial barrier function during vascular development and protects intraplaque microvessels against haemorrhaging in advanced atherosclerotic lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Recent work from Haasdijk and colleagues with a distinct thsd1 morpholino has independently confirmed our zebrafish results. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Recent work from Haasdijk and colleagues with a distinct thsd1 morpholino has independently confirmed our zebrafish results. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Mouse ortholog (TMTSP) shares 78.6% homology with the human protein (Dc et al, ). The first functional study of the gene identified THSD‐1 protein as an regulator factor of endothelial barrier function that promote stability of advanced lesions with intraplaque haemorrhaging by retaining the vascular integrity of the intimal neovascualture (Haasdijk et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Plaque inflammation also triggers smooth muscle cell loss and the production of matrix metalloproteinases (MMP) that weaken the fibrous cap, predisposing it to plaque rupture [ 2 , 5 ]. The thick necrotic acellular lipid core becomes increasingly hypoxic, stimulating angiogenesis, with the formation of immature microvessels prone to intra-plaque haemorrhage (IPH) [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%